PERAN PENELITI BALAI PENELITIAN DAN PENGEMBANGAN BUDIDAYA AIR PAYAU DALAM PUBLIKASI KARYA TULIS ILMIAH - Syarianah Syarianah (Jurnal Pari, 2015)
Kajian dilakukan untuk mengetahui konstribusi karya tulis ilmiah peneliti di Balai Penelitian dan Pengembangan Budidaya Air Payau Maros (BPPBAP) terhadap publikasi ilmiah, dilakukan kajian terhadap lima media publikasi yaitu: Jurnal Riset Akuakultur, Indonesian Aquaculture Journal, Media Akuakultur, Prosiding Forum Inovasi Teknologi Akuakultur, Prosiding Sekolah Tinggi Perikanan, dan Prosiding Hangtuah selama 5 tahun dari 2009 s/d 2013. Metode menggunakan analisis dokumen. Hasil kajian menunjukkan bahwa kontribusi karya tulis ilmiah peneliti BPPBAP bervariasi, yaitu pada tahun 2012 130 kti, tahun 2009 124 kti, tahun 2013 112 kti, tahun 2011 98 kti dan tahun 2010 93 kti. Kontribusi peneliti berdasarkan jenjang fungsional adalah peneliti pertama sebanyak 49 kti, peneliti muda 112 kti, peneliti madya 207 kti, dan peneliti utama 189 kti. Sebaran berdasarkan media publikasi yaitu Prosiding FITA sebanyak 197 kti, Prosiding Seminar STP sebanyak 169 kti, Prosiding Seminar HangTuah sebanyak 107 kti, JRA sebanyak 59 kti, IAJ sebanyak 13 kti, dan Media Akuakulture sebanyak 12 kti. Kontribusi kti berdasarkan kelti yaitu kelti keteknikan sebanyak 180 kti, kelti sumberdaya 133 kti, keltipathologi 91 kti, kelti bioteknologi 84 kti, dan kelti nutrisi 69 kti. Sepuluh peringkat peneliti yang memberi kontribusi terbanyak adalah Ansari dengan jumlah 27 kti, Arifuddin 26 kti, Brata 25 kti, Machluddin dan Suardi masing-masing 22 kti, Mudian 21 kti , Akhmad 20 kti, dan Utojo 18 kti, Erfan dan Markus masing-masing 17 kti.The study was done to understand the contribution that the researchers at the Institute for Brackish Water Aquaculture Research and Development (BBPBAP) to the scientific papers publication. The study focused on five medium of publication namely: Aquaculture Research Journal (Jurnal Riset Akuakulture), Indonesian Aquaculture Journal, Media Akuakultur, Prosiding Forum Inovasi Teknologi Akuakultur, Prosiding Sekolah Tinggi Perikanan and Prosiding Hang Tuah for the period of 5 years from 2009 to 2013. Method of analyses is literary review. The study shows that BPPBAP researchers contribution to scientific papers publication vary from 130 scientific papers in 2012, 124 scientific papers in 2009, 112 scientific papers in 2013, 98 scientific papers in 2011, and 93 scientific papers in 2010. Researchers contribution from the perspective of functional position level are: first researchers as many as 49 scientific papers, young researchers as many as 112 scientific papers, medium researchers as many as 207 scientific papers, and prime researchers as many as 189 scientific papers. Distribution based on medium of publication includes Prosiding FITA with 197 scientific papers, workshop proceeding from Fishery High School as many as 169 scientific papers, Hang Tuah Workshop proceeding as many as 107 scientific papers, Journal Riset Akuakulture as many as 59 scientific papers, Indonesian Aquaculture Journal as many as 13 scientific papers, and Media Aquaculture as many as 12 scientific papers. Scientific papers contribution from research group includes technical research group with 180 scientific papers, resources research group with 133 scientific papers, pathology research group with 91 scientific papers, biotechnology research group with 84 scientific papers, and nutrition research group with 69 scientific papers. The top ten rank of researchers with most contribution to scientific papers publication are Ansari with 27 scientific papers, Arifuddin with 26 scientific papers, Brata with 25 scientific papers, Machluddin and Suardi each contributed 22 scientific papers, Mudian with 21 scientific papers, Akhmad with 20 scientific papers and Utojo with 18 scientific papers while Erfan and Markus each contributed 17 scientific papers.